Semiautomatic volumetry of the temporal lobes of the brain and correlation with electroencephalography results in dogs with assumed idiopathic epilepsy - Paulina Kinga Drobot; Aleksandra Banasik; Karolina Owsińska‐Schmidt; Marcin Wrzosek; Przemysław Podgórski (Journal of Veterinary Internal Medicine)
Abstract Background Lesions causing refractory epilepsy, often associated with temporal lobe epilepsy (TLE), can be undetectable on standard magnetic resonance imaging (MRI) in dogs. Automated brain volumetry, widely used in human medicine, can now be applied in veterinary medicine because of the availability of brain atlases. Objectives This study aimed to develop an automatic volumetry method, translate the outcomes into the assessment of temporal lobe volumes in dogs with idiopathic epilepsy, and correlate the results with the electroencephalography (EEG) data of epileptiform discharges (EDs). Animals Thirty‐one dogs of various breeds with dominant temporal lobe discharge. Methods Retrospective, observational study. The MRI and EEG examination results of dogs referred for neurological diagnosis data between 2016 and 2021 were retrospectively analyzed. An automated volumetry method was developed, which allowed the evaluation of temporal lobe volumes of the dogs. The asymmetric ratio (AR) was then estimated, and the results were correlated with the EEG EDs. Results 12/31 (38%; 95% CI: 21.8%‐57.8%) dogs had an asymmetric ratio >6%. Among them, reduction in temporal lobe volumes correlated with the side of the EEG EDs in 7 cases. There was no statistical correlation between temporal lobe volume changes and ED location. Conclusions and Clinical Importance Preliminary volumetric analysis of the temporal lobes indicates the presence of volume differences between the lobes in some dogs with idiopathic epilepsy. Diagnosis of TLE in dogs based on MRI volumetry in correlation with EEG examination, especially for dogs with drug‐resistant epilepsy, can influence the development of new therapeutic options, such as surgery.